Effect on Strength Properties of Concrete Containing Seashell Powder as a Partial Substitution of Fine Aggregate and Silica Fume used as Admixture - S, Pragadeesan; S, Harishankar (International Journal of Engineering and Technology, 2018)
Sand is the most normally utilized fine aggregate in construction industry for the generation of concrete. The present scenario is in such a way that the cost of sand reached new heights and the demand for sand is also exhaustive. The replacement of the sand has a lot of constraints. Seashells are composed of calcium carbonate or chitin can be suitable alternative. It is used as a replacement of fine aggregate by 2%, 4%, 6%, 8%, and 10% for M20 grade concrete. Further 15% and 20% replacements are made. Silica fume is a ultrafine powder gathered as a result of silicon and ferrosilicon compound generation and the principle field of use is as pozzolanic material. It is used as an admixture by 5% to 10% of weight of cement to improve the strength properties. Concrete cubes and cylinders with mentioned proportion and conventional concrete are casted. Mechanical properties are evaluated by conducting compressive strength and split tensile strength tests.Â Â